Anti-arthritic Activity of Methanolic Extract and Various Fractions of Trigonella foenum-graecum Seed: An In-vitro Study - Trivedi, Rahul (International Journal of Pharmaceutical & Biological Archive, 2017)
Inflammation is a complex biological response to harmful stimuli, pathogens, irritants characterized by redness, warmth, swelling and pain. It is the response of body to inactivate or destroy the invading organisms, to remove the irritants & set the stage for tissue repair. Trigonella foenum-graecum (TFG) is one of the oldest Ayurvedic medicinal plants, used in traditional Chinese medicine and as dietary spice. The aim of our study was to evaluate the in-vitro anti-arthritic activity of methanolic extract and their fractions. The anti-arthritic activity was evaluated by protein denaturation method and proteinase inhibitory activity. In protein denaturation method, the percentage inhibition for methanolic extract was found to be 39.70 %. The petroleum ether and n-butanolic fraction of methanolic extract were shown 44.11 & 50.0 % inhibition respectively. Similarly, in proteinase inhibitory activity, methanolic extract showed 41.50 % inhibition and petroleum ether and n-butanolic fraction of methanolic extract were shown 47.16 & 50.94 % inhibition respectively at 500Î¼g/ml. The Diclofenac sodium was used as a standard drug in both models and shown greater activity as compared to petroleum ether and n-butanolic fraction. In conclusion, we found that TGF showed best activity in proteinase inhibitory model as compared to protein denaturation method.